2015
DOI: 10.1111/nyas.12768
|View full text |Cite
|
Sign up to set email alerts
|

B cells generated by B‐1 development can progress to chronic lymphocytic leukemia

Abstract: B cells generated early during fetal/neonatal B-1 development in mice include autoreactive cells with detectable CD5 upregulation induced by B cell receptor (BCR) signaling (B1a cells). A fraction of B1a cells are maintained by self-renewal for life, with the potential risk of dysregulated growth and progression to chronic lymphocytic leukemia (CLL)/lymphoma during aging. In studies using the Eμ-hTCL1 transgenic mouse system, it became clear that this B1a subset has a higher potential than other B cell subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Aspects of what we discuss below have also been previously reviewed as part of two presentations at a recent meeting devoted to B1 B cells .…”
Section: A Word On Nomenclaturementioning
confidence: 99%
“…Aspects of what we discuss below have also been previously reviewed as part of two presentations at a recent meeting devoted to B1 B cells .…”
Section: A Word On Nomenclaturementioning
confidence: 99%
“…These findings suggest a role for IκBε in the generation or expansion of B1 progenitor pool. BCR signaling plays an instructive role in B1a cell lineage determination and maintenance 28,30,44,45 . In addition, recent studies showed that BCR signaling cooperates with TLR signaling in controlling expansion and activation of B1a B cells [46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results may therefore suggest a crucial link between Ikaros loss and B1 cell-associated ALL. Finally, as CD5 ϩ B1 cells have been implicated in chronic lymphoid leukemia (CLL) (67), Ikaros may also act as a tumor suppressor in B1 cell-related CLL.…”
Section: Discussionmentioning
confidence: 99%